Pengaruh Jumlah Lubang Injektor Terhadap Performa Motor Yamaha New Vixion 150 CC - Handika Adi Pratama; Yoyok Winardi; Kuntang Winangun (KOMPUTEK, 2023)
For now the development of EFI (Electronic Fuel Injection) motorcycle engines for motorcycle engines to improve engine performance. The injector functions as a fuel sprayer inlet (intake manifold). This research was conducted to determine the effect of the number of injector holes on engine performance. The research method used was an experimental method carried out in the laboratory and using a Yamaha New Vixion 150 cc motorcycle with Pertalite fuel and using 4 hole, 6 hole and 10 hole injectors to determine the effect on its performance. This study used a Dynamometer (Dynotest) to determine the results of torque, power and the Cartec CET 210 series tool to determine the results of exhaust emissions and a measuring cup to determine the results of fuel consumption. The results showed that the maximum torque indicated on the 6-hole injector was 14.18 Nm compared to the 4-hole 13.36 Nm and 10-hole 5.83 Nm. The maximum power on the 6 hole injector is 15.18 HP compared to 4 holes 14.38 HP and 10 holes 4.80 HP. The best exhaust emissions from the 6-hole injector are CO2 12.7%, O2 6.53%, HC 428 ppm. Fuel consumption 4 holes 18.2 ml/minute, 6 holes 24.2 ml/minute, 10 holes 39.7 ml/minute. From the research it can be concluded that the 6-hole injector is a good size for the performance of the 150 cc Yamaha New Vixion motorbike.